A novel method for initial contact detection in treadmill running using side rail reflective marker - Hassmann, M.; Stadlbauer, A.; Kornfeind, P.; Stafilidis, S. (ISBS Proceedings Archive (Michigan), 2017)
Treadmill running analysis is often preferred to overground running due to the small observation volume. Splitting the cyclic running motion into single cycles requires the robust detection of common features identifying the initial contact (IC). Kinematic features such as HEEL marker velocity zero-crossing (ZC) in vertical or anteroposterior direction are proposed in literature. In this study (n = 14 male, 3.5 m/s, 3 right steps, 8 VICON MX cameras, 250 fps) a novel treadmill mounted marker (TREA) is compared to these two features. TREA vertical velocity ZC appears (6.8 ± 12.8) ms after HEEL anteroposterior ZC and can therefore be used as an easy-to-use feature for IC detection in treadmill running. HEEL vertical velocity ZC is to be doubted as it appears (59.0 ± 19.7) ms later than TREA vertical velocity ZC.